One-pot Ugi-azide and Heck reactions for the synthesis of heterocyclic systems containing tetrazole and 1,2,3,4-tetrahydroisoquinoline - Niu, Jiawei; Wang, Yuhui; Yan, Shenghu; Zhang, Yue; Ma, Xiaoming; Zhang, Qiang; Zhang, Wei (Beilstein Journal of Organic Chemistry, 2024)
A new method for the synthesis of heterocyclic systems containing tetrazole and tetrahydroisoquinoline is developed via the performance of one-pot Ugi-azide and Heck cyclization reactions. The integration of the multicomponent and post-condensation reactions in one-pot maximizes the pot-, atom-, and step-economy (PASE).
Keywords: Heck reaction; one-pot; tetrahydroisoquinoline; tetrazolo-pyrazino[2,1-a]isoquinolin-6(5H)-ones; tetrazole; Ugi-azide reaction